(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
Foraminiferal content from the type section of the Calcare del Predil, Early Carnian in age, is here firstly reported. Dolomites, dololimestones and blackish limestones alternate black shales, marls and marly limestones; in addition turbiditic deposits and debris flow consisting of calcirudites and thin to coarse calcarenites occur in the stratigraphical unit. The bottom of the Rio del Lago Formation was also investigated from a micropaleontological point of view. Nineteen taxa were classified; they are mainly represented by Aulotortinae Zaninetti, Lamelliconinae Zaninetti et al., Triadodiscinae Zaninetti, Turriglomininae Zaninetti and Ophthalmidiidae Wiesner. Furthermore, some Ammodiscidae Reuss, "Trochamminidae" Schwager, Piallinidae Rettori & Zaninetti, Duostominidae Brotzen and rare Lagenina Delage & Hérouard have been recorded. Undetermined encrusting foraminifers also occur. The specimens referable to the superfamily Involutinacea Btschli are dominant and represent the 4O% of the finely grained laminas inside the black limestones. The turriglominas occurring in the muddy lithotypes pertain to the morphogroup which is considered as typical of basinal environment. The occurrence almost constant in the micritic limestones of the ophthalmidiid Gsolbergella spiroloculiformis (Oravecz-Scheffer) (few specimens) leed to suggest this species as inhabitant basinal environment also. Two Julic species of the Austriacum zone are firstly reported from the Aon zone (Cordevolian Auct.) and the suprageneric position of the genus Prorakusia di Bari & Laghi is also discussed.